A CORRELATION STUDY OF BLOOD HBA1C WITH FASTING AND POSTPRANDIAL BLOOD GLUCOSE - KUMAR, PANKAJ; NAGDEOTE, ABHAY NILKANTH; GUPTA, PARUL; JADHAO, AVINASH N (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aimed to evaluate the correlation between raised blood sugar and glycated hemoglobin (HbA1c), a gold standard test for the assessment of glycemic control. Serial monitoring of HbA1C in diabetes mellitus helps in the prevention of microvascular and macrovascular complications. Methods: We retrospectively reviewed the laboratory reports of 397 patients who visited the hospital for various reasons. There were 195 males and 202 females in the study group. We evaluated the correlation between HbA1c and two indicators of glycemic control: fasting blood glucose (FBG) and postprandial blood glucose (PPBG). Results: Both FBG and PPBG showed a significant positive correlation with HbA1c. However, PPBG had a stronger correlation with HbA1c than FBG. The Spearman’s correlation coefficient (r) was 0.610 (p<0.05) for FBG and HbA1c and 0.683 (p<0.05) for PPBG and HbA1c. Conclusions: PPBG was a better predictor of HbA1c than FBG. PPBG may be an alternative marker of HbA1c for the management and monitoring of diabetes mellitus.